2015
DOI: 10.1353/etc.2015.0009
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Teacher-Directed Opportunities to Respond on Student Outcomes: A Systematic Review of the Literature

Abstract: Research indicates that increasing teacher-directed opportunities to respond (TD-OTR) positively impacts student outcomes. Prior reviews of the empirical literature focused on outcomes for students with emotional behavioral disorders or on TD-OTRs as one of many classroom-management practices; however, prior reviews did not examine effects of TD-OTRs solely within the class-wide context. For the present review, we (a) examined class-wide TD-OTR research (i.e., screened a total of 527 unique abstracts and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(98 citation statements)
references
References 27 publications
2
96
0
Order By: Relevance
“…Research studies have determined that for students with high incidence disabilities (i.e., learning disabilities), a suggested a rate of approximately three to five teacher-directed OTR per minute are associated with positive student outcomes [22]. When teachers generated OTR, they increased the likelihood of desired responses from students, whether through incorporated strategies of presentation materials, asked questions, or corrected student answers [23].…”
Section: Opportunities To Respondmentioning
confidence: 99%
“…Research studies have determined that for students with high incidence disabilities (i.e., learning disabilities), a suggested a rate of approximately three to five teacher-directed OTR per minute are associated with positive student outcomes [22]. When teachers generated OTR, they increased the likelihood of desired responses from students, whether through incorporated strategies of presentation materials, asked questions, or corrected student answers [23].…”
Section: Opportunities To Respondmentioning
confidence: 99%
“…OTRs are opportunities for students to "say, write, or do things" (Archer & Hughes, 2011, p. 131), and they have multiple benefits. They increase student engagement and reduce negative behavior; they also allow teachers to closely monitor student learning and understanding (Archer & Hughes, 2011;MacSuga-Gage & Simonsen, 2015). There are multiple ways teachers can increase students' rate of response, including incorporating group responding techniques like choral responses or use of response cards or using peer responding through activities like think-pair-share (Brownell et al, 2012).…”
Section: Interactionsmentioning
confidence: 99%
“…In a review of research on teacher-directed OTRs, MacSuga-Gage and Simonsen (2015) found that response cards were more effective than waiting for individual volunteers in increasing student academic outcomes and that more frequent rates of OTRs resulted in higher student achievement. Based on this review, they recommend a rate of 3.00 to 5.00 OTRs per minute as being the most beneficial for student learning, with lower rates being more realistic when using techniques like response cards.…”
Section: Interactionsmentioning
confidence: 99%
See 2 more Smart Citations